2018
DOI: 10.3389/fonc.2018.00130
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Oncology in the 21st Century: Prospective Randomized Trials That Changed Practice… or Didn’t!

Abstract: In a two-part article published in 2009, we discussed the limitations of conventional radiation therapy, the challenges of studying new technologies in radiation oncology, and summarized the state-of-the science for various malignancies (1, 2). Here, we summarize some of the most important prospective, randomized trials that during the intervening years have attempted to improve the tumor control and/or decrease the adverse effects of radiation therapy. For consistency, we have focused here on the null and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In recent years, several practice-changing studies have been published that significantly impact the recommendation for clinical management of BC [ 22 ]. However, to date, one of the greatest challenges of modern oncology is the transferability of “knowledge” and “know-how” from Evidence-Based Medicine (EBM) to RWE [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several practice-changing studies have been published that significantly impact the recommendation for clinical management of BC [ 22 ]. However, to date, one of the greatest challenges of modern oncology is the transferability of “knowledge” and “know-how” from Evidence-Based Medicine (EBM) to RWE [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63] For many common cancers where RT is a crucial component of the first-line, curative-intent treatment, local failures (eg, in glioblastoma) or the lack of pathological complete response (eg, in rectal cancer) remain frustratingly common. 64 Our understanding of why the tumor is controlled in some patients but not in others remains limited. 61 Molecular characterization of the tumor before, during, and after irradiation is important for increasing our understanding and developing novel interventions that can be incorporated during or shortly after a course of irradiation to prevent the persistence or recurrence of tumors.…”
Section: Clinical Research and Heterogeneity-based Treatmentmentioning
confidence: 99%
“…The number of cancer cases also highly increased in China, reaching 4,568,754, compared to 2018 statistical data ( Bray et al, 2018 ; Sung et al, 2021 ). The analysis of cancer therapy worldwide indicated that almost half of cancer patients received radiation treatment ( Bernier, 2016 ; Zakeri et al, 2018 ). Radiotherapy is designed to kill tumor cells using high-energy ionizing radiation, such as gamma rays and X-rays, and electron and proton beams.…”
Section: Introductionmentioning
confidence: 99%
“…In sensitized cancers, radiotherapy delivers a highly desirable elimination of cancer cells, although the cancer-free outcome is hard to reach. During radiotherapy treatment, TME impacts the successful elimination of tumor cells and may negatively contribute the treatment and patient survival ( Zakeri et al, 2018 ; Pontoriero et al, 2023 ). Research data confirmed that radiotherapy triggers various anti-cancer changes in TME and affects anti-tumor responses.…”
Section: Introductionmentioning
confidence: 99%